EVALUATION OF A SILAGE PRODUCED BY MIXTURE OF RESIDUES OF CASSAVA (MANIHOT ESCULENTA), POTATO (SOLANUM TUBEROSUM), EGGPLANT (SOLANUM MELONGENA) AND WATERMELON (CITRULLUS LANATUS), GENERATED IN SUPERMARKETS (Journal of Namibian Studies : History Politics Culture, 2023)
This paper evaluates the physical, chemical and microbiological composition of silage obtained from mixtures of plant residues. The research was experimental with a quantitative approach, the data obtained from the response variables were analyzed using statistical tools for the subsequent interpretation of the data. For the execution of the experiment, plant residues of potatoes, cassava, eggplant and watermelon discarded in supermarkets in the city of Valledupar were used. For the production of silage, a completely random experimental design was applied with four treatments and three repetitions. The best treatment was selected through the analysis of variance (ANOVA) and comparison of means through the Tukey test. Three of the four alternatives for the production of silage are viable since they carry the process in a correct way because the pH values given suggest that there is an optimal production of lactic acid bacteria. The tests carried out comply with adequate characteristics in treatments two, three and four. Treatments containing the highest percentage of cassava showed the best values in fiber, carbohydrates and protein. While the silages that contained in greater proportion the potato were the richest in moisture.